Ecological niches for colorectal cancer stem cell survival and thrival - Che, Jiayun; Yu, Shiyan (Frontiers in Oncology, 2023)
To date, colorectal cancer is still ranking top three cancer types severely threatening lives. According to cancer stem cell hypothesis, malignant colorectal lumps are cultivated by a set of abnormal epithelial cells with stem cell-like characteristics. These vicious stem cells are derived from intestinal epithelial stem cells or transformed by terminally differentiated epithelial cells when they accumulate an array of transforming genomic alterations. Colorectal cancer stem cells, whatever cell-of-origin, give rise to all morphologically and functionally heterogenous tumor daughter cells, conferring them with overwhelming resilience to intrinsic and extrinsic stresses. On the other hand, colorectal cancer stem cells and their daughter cells continuously participate in constructing ecological niches for their survival and thrival by communicating with adjacent stromal cells and circulating immune guardians. In this review, we first provide an overview of the normal cell-of-origin populations contributing to colorectal cancer stem cell reservoirs and the niche architecture which cancer stem cells depend on at early stage. Then we survey recent advances on how these aberrant niches are fostered by cancer stem cells and their neighbors. We also discuss recent research on how niche microenvironment affects colorectal cancer stem cell behaviors such as plasticity, metabolism, escape of immune surveillance as well as resistance to clinical therapies, therefore endowing them with competitive advantages compared to their normal partners. In the end, we explore therapeutic strategies available to target malignant stem cells.